Pediatric Nurse' Views About Staff Safety - Muradiye Aldem; Fatma Taş Arslan (Association of Nurse Managers, 2018)
INTRODUCTION: The study was conducted as a descriptive study to determine the nurses' views on employee safety, risk perception scores and related factors METHODS: The study was conducted between March and May 2014 in four hospitals located in the city center of Konya province. 169 nurses working in pediatric clinics were included in the study. A questionnaire prepared by the researcher was used to collect the data. The analysis of the data was evaluated by computer, number, percentage, mean, ANOVA, Tukey HSD, t test. RESULTS: It was determined that the average age of the nurses was 30.40 +- 6.21 and 88.2% of the nurses received information about working safety. When the working safety areas of nurses are evaluated; (69.3%) in the field of biosecurity, pain in the lower extremity in the area of ergonomic safety (90.3%), noises in the field of physical security (95.3%), exposure to disinfectants in the field of chemical safety (68.6% 5), and fatigue (93.5%) in the psycho-social security field was found to be the most experienced. DISCUSSION AND CONCLUSION: Nurses are perceived to be at the highest ergonomic and lowest risk of chemical safety.